2022
DOI: 10.3390/cancers14020433
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Management of Grade 1 and 2 Pancreatic Neuroendocrine Tumors

Abstract: Pancreatic neuroendocrine tumors (p-NETs) are rare tumors with a recent growing incidence. In the 2017 WHO classification, p-NETs are classified into well-differentiated (i.e., p-NETs grade 1 to 3) and poorly differentiated neuroendocrine carcinomas (i.e., p-NECs). P-NETs G1 and G2 are often non-functioning tumors, of which the prognosis depends on the metastatic status. In the localized setting, p-NETs should be surgically managed, as no benefit for adjuvant chemotherapy has been demonstrated. Parenchymal spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 141 publications
0
3
0
1
Order By: Relevance
“…An exophytic or pedunculated PanNET is also an atypical finding, such as in the current case (6,7). Although the exact prevalence of the exophytic PanNET has not been reported, given that enucleation is endorsed as a surgical treatment option for exophytic PanNET, it might not be highly uncommon in clinical practice (8,9). In such cases, ambiguous tumor origin demands differential diagnoses, including peripancreatic gastrointestinal stromal tumor, peripancreatic paraganglioma, solitary fibrous tumor, and even lymph node (7).…”
Section: Discussionmentioning
confidence: 65%
“…An exophytic or pedunculated PanNET is also an atypical finding, such as in the current case (6,7). Although the exact prevalence of the exophytic PanNET has not been reported, given that enucleation is endorsed as a surgical treatment option for exophytic PanNET, it might not be highly uncommon in clinical practice (8,9). In such cases, ambiguous tumor origin demands differential diagnoses, including peripancreatic gastrointestinal stromal tumor, peripancreatic paraganglioma, solitary fibrous tumor, and even lymph node (7).…”
Section: Discussionmentioning
confidence: 65%
“…Поскольку убедительных данных об онкологических преимуществах энуклеации нет, U. Marchese и соавт. полагают, что ее не следует предлагать в качестве альтернативы радикальной резекции [39].…”
Section: энуклеацияunclassified
“…Even though there existed numerous treatment options for PanNENs, surgery remained the cornerstone of treatment, which has been proved to be with survival benefits (17)(18)(19)(20). Some studies even concluded that cancer-directed surgery can also provide improved survival outcomes in patients with distant diseases (21)(22)(23)(24)(25).…”
mentioning
confidence: 99%